2017
DOI: 10.1007/s00059-017-4633-7
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular twist in hypertrophic cardiomyopathy

Abstract: Decreased GLPS and increased twist were predictive of NsVT in HCM patients. Parameters that can easily be measured with STE can help detect patients who may develop arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Changes in LV rotation have been observed at the early phase of many cardiac diseases, and they even precede changes in longitudinal and circumferential strain (18). Aging, hypertension, hypertrophic cardiomyopathy and aortic stenosis are all characterized by increased apical rotation and delayed rotation with longer untwisting (18)(19)(20)(21)(22). Anthracycline treatment has induced a decline in both apical and basal rotation along with an overall twist becoming declined and delayed (23).…”
Section: Changes In Apical Strain In the Follow-up According To Brementioning
confidence: 99%
“…Changes in LV rotation have been observed at the early phase of many cardiac diseases, and they even precede changes in longitudinal and circumferential strain (18). Aging, hypertension, hypertrophic cardiomyopathy and aortic stenosis are all characterized by increased apical rotation and delayed rotation with longer untwisting (18)(19)(20)(21)(22). Anthracycline treatment has induced a decline in both apical and basal rotation along with an overall twist becoming declined and delayed (23).…”
Section: Changes In Apical Strain In the Follow-up According To Brementioning
confidence: 99%
“…We read with great interest the article by Candan and colleagues [1]. The authors have found an independent association of increased left ventricular twist and decreased global longitudinal strain (GLS) with the occurrence of nonsustained ventricular tachycardia (NSVT) during Holtermonitoring inpatients with hypertrophic cardiomyopathy (HCM).…”
Section: Speckle Tracking Imaging In Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…We are pleased with the authors' interest in our article titled "Left ventricular twist in hypertrophic cardiomyopathy: predictors of nonsustained ventricular tachycardia" published in Herz [1], and we would like to thank them for their contribution.…”
mentioning
confidence: 99%